Išorinė atviroji sandūra ir priebalsių kiekybė bendrinėje lietuvių kalboje - Tankevičiūtė, Marytė; Strimaitienė, Marija (Kalbotyra, 1987)
An instrumental experiment was carried out in order to see how the duration and intensity of consonants are influenced by external open juncture in Standard Lithuanian. The external open juncture of a vowel and a consonant, two identical consonants and clusters of different consonants was investigated. It turned out that this phenomenon is realized phonetically and is a real optional phonological element only in consonant clusters. A key role is played here by the duration of segments.